Information in Operation: Probability - Joseph E. Brenner (Proceedings, 2022)
This paper proposes an informational approach to probability based on a non-semantic, non-propositional and non-truth-functional logic of real processes and systems, according to which they interact and evolve—Logic in Reality, LIR. Its fundamental principle is that the contradictory or opposing informational elements of complex real processes move from states that are primarily potential to ones that are predominantly actual, alternately and reciprocally, without going to the abstract, ideal limits of zero or one. LIR provides a thread between the different sciences and constitutes a bridge between the ontological aspects of logic, science and philosophy.